2007
DOI: 10.1080/10409280701283460
|View full text |Cite
|
Sign up to set email alerts
|

Age of Entry to Kindergarten and Children's Academic Achievement and Socioemotional Development

Abstract: Research Findings-Data on more than 900 children participating in the National Institute of Child Health and Human Development Study of Early Child Care were analyzed to examine the effect of age of entry to kindergarten on children's functioning in early elementary school. Children's academic achievement and socioemotional development were measured repeatedly from the age of 54 months through 3rd grade. With family background factors and experience in child care in the first 54 months of life controlled, hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…In each instance, children who were older when they entered kindergarten scored higher on measures of academic achievement and psychomotor development as well as on teachers' ratings of social competence. These findings are consistent with other studies' findings (Crosser, 1991;Gullo & Burton, 1992;NICHD, 2007). In studying the effect of age on kindergarten readiness, Zill and West (2001) found that teachers rated children who were older in their classes as exhibiting more of a positive approach towards school and were more persistent in completing tasks than were younger children.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In each instance, children who were older when they entered kindergarten scored higher on measures of academic achievement and psychomotor development as well as on teachers' ratings of social competence. These findings are consistent with other studies' findings (Crosser, 1991;Gullo & Burton, 1992;NICHD, 2007). In studying the effect of age on kindergarten readiness, Zill and West (2001) found that teachers rated children who were older in their classes as exhibiting more of a positive approach towards school and were more persistent in completing tasks than were younger children.…”
Section: Discussionsupporting
confidence: 82%
“…The chronological age at which children enter kindergarten has also been a focus of study relative to its effects on measures of kindergarten readiness (Crosser, 1991;Gullo & Burton, 1992;NICHD, 2007;Spitzer, Cupp, & Parke, 1995;Stipek, 2002). In general, children who enter kindergarten at younger ages score lower on measures of academic achievement associated with kindergarten readiness as compared to children who are chronologically older.…”
Section: School Readiness and Biological Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…One solution is to incorporate an InsV which is correlated with the causal treatment but has no direct effect on the outcome variable so that the confounding effects are extracted by the InsVs. Authors of the original study found a positive effect from kindergarten through grade five in reading (Zhong and Hoxby, 2012), and that an ideal InsV could be the predicted relative entrance age (interaction between a child's birthday and the statelevel cut-off date for the school enrollment), as this variable is highly correlated with the actual relative age, but uncorrelated with the causal outcome itself or other unobserved determinants of academic achievements such as maturity or aptitude (Allhusen et al, 2007). With the inclusion of the predicted relative entrance age as the InsV, the local average treatment effect (LATE) is the causal effect of the early childhood relative age on reading achievement for children who enroll in the same year that meets the state-level requirements.…”
Section: Example 1-early Childhood Reading Achievementmentioning
confidence: 99%
“…Diğer taraftan başarıda temel belirleyicinin yaş olmadığı (NICHD, 2007) bunun yanı sıra aile, sosyo-ekonomik durum gibi değişkenlerin de önemli olduğu vurgulanmaktadır. Furlong ve Quirk'e (2011) göre öğrencilerin okula hazır oluşları, onların daha sonraki başarılarında, yaştan daha fazla etkilidir.…”
Section: Tartışma Ve Sonuçlarunclassified